A Narrative Review of Physical Activity and Exercise during Pregnancy: Nurse’s Role - Sirikanok Klankhajhon; Anonthasha Sthien (The Journal of Palembang Nursing Studies, 2022)
Obesity is an important global health issues in pregnancy that impact on pregnant women and newborn such as gestational diabetes mellitus, and cardiovascular diseases. The scoping review six stages is used to review an exercise during pregnancy, which is associated to potential maternal and newborn’s physical, psychological and social health aspects both short and long terms. The prescription of exercise during pregnancy for low risk pregnant women without any contraindications should take moderate level of exercise at least 3 times a week, at least 30 minutes or more of accumulated exercise a day, which include a 5-10 minutes warm up and cool down period, 20-30 minutes exercise from protocol: muscular workouts and/or cardiovascular training. Pregnant women should exercise as muscular workouts and cardiovascular training and unsafe activities should be avoided. Nurses’ role support pregnant women to enhance knowledge of exercise and increase exercise behaviour during pregnancy through nursing process at antenatal care clinic.